Corporate crime - Slapper, Gary (1999)
This book offers a comprehensive analysis of a subject which is becoming of increasing concern and debate amongst criminologists. The key element in its approach is an examination of corporate crime in the broad contexts of theoretical criminology, applied criminology and criminal justice. Chapters in the book set out the types and nature of corporate crime, discuss the various theories that have been developed to explain it, critically examine major developments, (such as the increasing size and power of corporate organisations) and consider questions of the policing and punishment of corporate crime